Stratigraphic column of the Pucara Group in Chinchao section-Huanuco - Reyes Rivera, Luis (2012)
The stratigraphic column of the Pucara Group in Chinchao -Huánuco section is 3500 m thick and is predominantly carbonated , is one of the most comprehensive in the region, still visible its base and top , comprising the Chambara , Aramachay and Condorsinga formations. The Chambara Formation consists of limestones biomicrítica , biopelmicritica , intraesparítica and dolomites with subparallel laminations, microcalciesferas concentrations of chert , stylolitic structures , calcite veinlets and traces of pyrite , its middle part contains interbedded black and carbonaceous shales. The Aramachay Formation consists of silty loams lajosas , interspersed with black carbonaceous shale Arietites Sinemurian , occur on your bumper hydrothermal alteration type "zebra" . Finally, Condorsinga biomicrite Formation consists of gray to light gray . The mineral potential is given by the "zebra" structure related to MVT deposits, and hydrocarbon potential for generating dark oil and black rocks .